Critical Succes Factors, Instructors' Characteristics and Accounting Information System Course Content - Lallo, Naseem Yuosif Hanna (2012)
Although an Accounting Information System (AIS) course is important to equip accounting students with adequate knowledge and skills, little research has investigated factors that should be considered in developing such course content. This scenario is obvious in Iraq, particularly because the education system deteriorated severely due to the civil war of the last several decades. To look for critical success factors, this study identified employers‟ needs, professional bodies, learning environment, and International Federation of Accounting Committee (IFAC) recommendations as factors that might influence AIS course content. This study considered instructors‟ characteristics as a moderating variable that could enhance the relationship between IFAC recommendations and AIS course content. The objectives of the study were the following: (1) to identify the critical success factors influencing AIS course content at Iraqi Higher Education Institutions (HEI), and (2) to investigate the moderating effect of instructors‟ characteristics on the relationship between IFAC recommendation and AIS course content. To achieve these objectives, 260 questionnaires were sent to accounting lecturers at different Iraqi HEIs of these instruments, 165 were returned, yielding a response rate of about 63.5%, but only 134 were usable. Multiple regression analysis was used to test the relationships between (and among) AIS course content and employers‟ needs, professional bodies, learning environment, and IFAC recommendations. The findings showed that personal traits, professional bodies, participatory learning and teaching methods and general information and communication technologies (ICT) knowledge had no significant influence on AIS course content whereas other dimensions such as core knowledge and Information Technology (IT) competency had significant influence. Hierarchical multiple regression was applied to investigate the moderating influence. The results show that IT competency and general ICT knowledge were not significant whereas IT control knowledge and general IT knowledge were significant.